Pancasila Leadership: The Contribution of Pancasila-Profiled Leadership Through Team Collaboration to Improve Lecturer Performance in Higher Education - Yusaini Yusaini; Tabrani ZA; Dedisyahputra Dedisyahputra; Indis Ferizal (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2026)
Negative phenomena in leadership have increasingly emerged, reflected in various cases indicating a crisis of morality and character. In recent times, leaders have been involved in cases of corruption, sexual harassment, drug abuse, infidelity, and other misconduct, largely due to noncompliance with governmental regulations and religious principles. Such forms of leadership can undermine teamwork and organizational performance across various institutions. This article examines the influence of Pancasila-profiled leadership behavior on teamwork and lecturer performance within State Islamic Religious Higher Education Institutions (Perguruan Tinggi Keagamaan Islam Negeri, PTKIN). To date, research has been limited in addressing the importance of leaders embodying Pancasila-based characteristics in their leadership practices. Therefore, this study differs from previous research, which generally focuses on managerial success without examining leadership behavior in depth. The research data were collected using a questionnaire that had previously undergone validity and reliability testing with 30 respondents. The data analysis employed a quantitative approach using Path Analysis statistical techniques, involving 90 respondents who are Heads of Study Programs within PTKIN. The findings reveal three key factors influencing lecturer performance in higher education. First, Pancasila-profiled leadership directly affects lecturer performance. Second, teamwork significantly influences lecturer performance. Third, Pancasila-profiled leadership also indirectly affects lecturer performance through teamwork. These findings are expected to serve as an important reference for leaders in Indonesia, particularly within PTKIN, to prioritize Pancasila-based leadership behavior. Such leadership is essential for fostering leaders and lecturers who adhere to state regulations and religious values, uphold noble character, embrace diversity, promote cooperation, and demonstrate creativity and independence to enhance higher education performance.